(3GdLhgQ Gdfaj aj GdQO Ydi GdHjgbis - (3CHh GdMSf YdGA GdOjf Ydj Hf YKeGf Hf EHQGgje Hf GdJQceGfj GdeGQOjfj,J (B750 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg (B: (3bGd (B: (3HGH efY GdJWgjQ HeG YOG GdeGA ef GdeGFYGJ GSJOd Ydi Pdc HMOjK CHj PQ (B: (3aEPG hLOJ GdeGA aCeSg LdOc s
(3BNQgG (B:s
(3ef HGH YOI Ce GdhdO (B: (3PcQ gPg GdeSCdI ai gPG GdHGH ZjQ efGSH hbO PcQgG GdHjgbi ajeG JbOe ai ChGNQ CHhGH GdYOI Je GdcJGH s
(3GdfSNI HgG MhGTs
(3LGA HBNQgG Cf GdeDda aQZ ef JHjV GdcJGH SfI (B747s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B311s
Keywords: (3GdMOjK h GdeUWdMs